Long Wavelength TCF-Based Fluorescent Probe for the Detection of Alkaline Phosphatase in Live Cells - Gwynne, Lauren; Sedgwick, Adam C.; Gardiner, Jordan E.; Williams, George T.; Kim, Gyoungmi; Lowe, John P.; Maillard, Jean-Yves; Jenkins, A. Toby A.; Bull, Steven D.; Sessler, Jonathan L.; Yoon, Juyoung; James, Tony D. (Frontiers in Chemistry, 2019)
A long wavelength TCF-based fluorescence probe (TCF-ALP) was developed for the detection of alkaline phosphatase (ALP). ALP mediated hydrolysis of the phosphate group of TCF-ALP resulted in a significant fluorescence ‘turn on’ (58-fold), which was accompanied by a colorimetric response from yellow to purple. TCF-ALP was cell permeable, which allowed it to be used to image ALP in HeLa cells. Upon addition of bone morphogenic protein 2, TCF-ALP proved capable of imaging endogenously stimulated ALP in myogenic murine C2C12 cells. Overall, TCF-ALP offers promise as an effective fluorescent/colorimetric probe for evaluating phosphatase activity in clinical assays or live cell systems.